An Interactive Session to Help Faculty Manage Difficult Learner Behaviors in the Didactic Setting - Benjamin H. Schnapp; Al'ai Alvarez; Jared Ham; Glenn Paetow; Sally A. Santen; Danielle Hart (Association of American Medical Colleges, 2018)
Introduction The transition to more active learning during residency didactics has made the skill of managing difficult learner behaviors essential: Just one learner exhibiting difficult behavior can derail the educational experience for the room. Many educators feel uncomfortable handling these learners in real time and after the session. Methods We created an interactive session for a mixed group of educators at a medical education boot camp. After learning about a framework for addressing difficult learner behaviors, participants were paired and presented with the case of a withdrawn learner. For each pair, the cause of the behavior was different. With one of the pair role-playing the learner, they were asked to identify the problem and solutions together. Multiple etiologies for the identical behavior reinforced the need to address underlying causes to create an effective plan for behavior change. Strategies to address difficult behaviors in real time were also discussed in large-group format. Results Participants gave the session a mean score of 4.5 out of 5, indicating a high likelihood of changing their teaching practice. Free-response comments remarked on the role-play's educational value and the enjoyability of the session overall. Discussion This session was effective in giving participants a framework for dealing with difficult learner behaviors, as well as hands-on practice with these skills. While this was a short (30-minute), single session, its success with participants with a wide variety of experience levels suggests it would be highly adaptable to other settings and may benefit from future expansion into the clinical setting.